1992
DOI: 10.1128/aac.36.5.938
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of cefprozil into human breast milk

Abstract: The excretion of cefprozil into breast milk in nine healthy, lactating female subjects was investigated. Each subject received a single 1,000-mg oral dose of cefprozil consisting ofcis and tramns isomers in an approximately 90:10 ratio. Serial blod, urine, and breast milk samples were collected and analyzed for the concentrations of the cis and trns isomers by a specific high-pressure liquid chromatography-UV assay. The mean pharmacokinetic parameters for both isomers were essentialy the same. The mean peak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Although LOD and LOQ of described method cannot be evaluated as much better than the LC‐MS method reported by Wang et al 27, our results were better than almost all of the previously published studies including some LC‐MS methods 19, 20, 24, 28. LOD and LOQ were reported between 0.05 and 20 μg/mL in the previous studies, whereas proposed method allowed about 0.03 and 0.09 μg/mL, respectively.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Although LOD and LOQ of described method cannot be evaluated as much better than the LC‐MS method reported by Wang et al 27, our results were better than almost all of the previously published studies including some LC‐MS methods 19, 20, 24, 28. LOD and LOQ were reported between 0.05 and 20 μg/mL in the previous studies, whereas proposed method allowed about 0.03 and 0.09 μg/mL, respectively.…”
Section: Discussioncontrasting
confidence: 69%
“…The explanation of this improvement was associated to the very low noise of the assays (about 0.25–0.50 mAU), which was interpreted as a total result of acetonitrile usage in mobile phase, high absorptivity of CPZ at 200 nm and avoiding use of buffers to maintain pH. In addition, literature search shows that 245 nm 31, 254 nm 24, and 280 nm 19, 20, 22, 25, 28–30 wavelengths were mainly preferred in UV‐based detections of CPZ. Method development studies exhibited that CPZ absorbs UV light about 79% less at 245 nm, 81% less at 254 nm, and 70% less at 280 nm when compared with 200 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, a population-based pharmacokinetic approach was applied to estimate the fluoxetine milk-to-plasma ratio and the exposure of infants to this drug through breast milk, assuming that plasma and milk drug concentrations are roughly parallel (Panchaud et al, 2011). However, the time course of drug concentrations in plasma and milk does not usually increase or decrease in parallel (Somogyi and Gugler, 1979;Shyu et al, 1992), and in these cases, the drug profiles cannot be explained by rapid equilibration. Further improvement of the predictive model to estimate the time profiles of drug concentrations in milk would be useful to minimize the exposure of breast feeding infants to drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[72,73,76,[78][79][80][81] In contrast, Blanco et al [40] observed measurable ceftazidime milk concentrations of 3.8 to 8.2 mg/L in the milk of 11 breast-feeding women who were administered ceftazidime 2g intravenously three times daily for 5 days. [72,73,76,[78][79][80][81] In contrast, Blanco et al [40] observed measurable ceftazidime milk concentrations of 3.8 to 8.2 mg/L in the milk of 11 breast-feeding women who were administered ceftazidime 2g intravenously three times daily for 5 days.…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%